Capturing the Invisible Attacks Recognition In industrial control system - V.Mariselvam, S.Arunthathi , K.Gowshika, M.Yazhini (International Journal of Modern Agriculture, 2021)
Industrial Control Systems(ICS)are systems the attrack ,industrialize, andmultifaceted frame and developmentes are part of vital industrial sectors that have an impactonourdailylives.Cybersecurityhasbecomeadifficultprobleminindustrial controlsystems (lCSs) as data network technologies are rapidly implemented.Dangerous attacks,such as machine malfunctions, rising ambient temperature, and unwanted gas particles beingreleased into the air,can occurduring these ICS operations.This projectuses wireless Zigbee technology to continuously track lCS parameters such as load voltage-current, loadcondition(noload/over-load),temperature,humidity,andgasleakage,aswellasfiredetection.Amicrocontroller-baseddeviceisusedtogatherandstoredataand make decisions based on the data, which includes cyber-attacks,computermalfunctions, andenvironmentalissues.Humanwellbeingisaffectedbyharshenvironmentalconditions.TheZigbee, IEEE 802.15.4 standard-based communication system is secure.Thisis used for wireless communication between the hardware circuit mounted at the local siteand the remote monitoring site computer.This approaches the efficacy of threshold valuesignature based detection versus the application of process analyticstospotattackin industrialcontrol infrastructure systems is compared in this project. The study that is beingsuggestedusesaalgorithmforpatternrecognitioncalled"Capturing-the-Invisible(CTI)"tofindclandestine processes at industrial management system records withdistinguish real-timeAttacks focused on a person’s behaviour. This device is extremely useful for ICS and factoryworkersand equipmentrescue andsafety.